(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper sheds light on the law of family and familial issues in Mesopotamia according to Hammurabi Law. In this line, the family was the basis in Mesopotamia and the Law of Hammurabi focused on all its related issues starting from engagement until marriage, children, adoption, betrayal, heritage, divorce, etc. Thus, we conclude that the family law in Mesopotamia was developed and focused on the issues of the family since it is the core of the society, which succeeds with its success and fails with its failure. Based on what has been said, this paper aims at showing the importance attributed by Hammurabi Law to the family in Mesopotamia, as it is the pillar of the society. In so doing, we used the historical descriptive method as it suits the nature of the study.